Links Between Accounting and Business Statistics - Motoryn, Ruslan (Relacje między rachunkowością a statystyką biznesu, 2010)
An accounting database harmonized with statistics, aimed at all categories of users, has been developed in Ukraine. A possibility to harmonize official accounting systems is stipulated by: the use of monetary indices; the use of economic categories in conceptual device; orientation at external information users; aggregation (consolidation, generalization) of received data; initiatives concerning constant increasing of quality of information. Those characteristics together with the absence of conceptual contradictions between these systems allow to talk about possibility of harmonization of accounting information.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 80-86
Keywords: links; accounting; business statistics